Matrix-Associated Autologous Chondrocyte Implantation Is an Effective Treatment at Midterm Follow-up in Adolescents and Young Adults. Issue 4 (25th April 2019) - Hoburg, Arnd; Löer, Ingo; Körsmeier, Konrad; Siebold, Rainer; Niemeyer, Philipp; Fickert, Stefan; Ruhnau, Klaus
Background: Autologous chondrocyte implantation (ACI) is an established method for treating cartilage defects in the knee of adult patients. However, less is known about its effectiveness in adolescents. Hypothesis: Third-generation matrix-associated ACI (MACI) using spheroids (co.don chondrosphere/Spherox) is an effective and safe treatment for articular cartilage defects in adolescents aged 15 to 17 years, with outcomes comparable with those for young adults aged 18 to 34 years. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 71 patients (29 adolescents, 42 young adults) who had undergone ACI using spheroids were evaluated retrospectively in this multicenter study. For adolescents, the mean defect size was 4.6 ± 2.4 cm 2, and the follow-up range was 3.5 to 8.0 years (mean, 63.3 months). For young adults, the mean defect size was 4.7 ± 1.2 cm 2, and the follow-up range was 3.8 to 4.3 years (mean, 48.4 months). At the follow-up assessment, outcomes were assessed by using validated questionnaires (Knee injury and Osteoarthritis Outcome Score [KOOS], International Knee Documentation Committee [IKDC] subjective knee evaluation form and current health assessment form, and modified Lysholm score), the magnetic resonance observation of cartilage repair tissue (MOCART) score, and if relevant, time to treatment failure. Safety was assessed by the treatment failure rate. Results: No significant difference between the 2 study groups was found for KOOS, IKDC, or MOCART scores, with all patients achieving high functional values. A significant difference was found in the modified Lysholm score, favoring the young adult group over the adolescent group (22.3 ± 1.9 vs 21.0 ± 2.4, respectively; P = .0123). There were no differences between the rates of treatment failure, with 3% in the adolescent group and 5% in the young adult group. Conclusion: Third-generation MACI using spheroids is a safe and effective treatment for large cartilage defects of the knee in adolescents at midterm follow-up. Outcomes are comparable with those for young adults after ACI.